Pengaruh Persepsi Harga, Kualitas Produk, Dan Brand Image Terhadap Keputusan Pembelian Produk Mie Instan Gaga Mie - Putri, Eryana; Gendalasari, Gen Gen; Fahsani, Donny Hendry (Jurnal Aplikasi Bisnis Kesatuan, 2023)
This study aims to: (1) to determine the effect of perceived price on purchasing decisions (2) to determine the effect of product quality on purchasing decisions (3) to determine the effect of brand image on purchasing decisions (4) to determine the effect of perceived price, product quality and Brand Image on Purchasing Decisions. The number of samples is 230 respondents using the formula Hair et all. The sampling method used is purposive sampling. The data analysis method used is multiple linear regression analysis to determine the effect of price perception, product quality and brand image on purchasing decisions of Gaga Mie Instant Noodles in Bogor City. Data testing was carried out using the Software Statistical Package For The Social Scientist (SPSS).Based on the test results, the following data were obtained: (1) there was no effect of perceived price on purchasing decisions (2) there was an effect of quality on purchasing decisions (3) there was an influence of brand image on purchasing decisions (4) there was an influence between perceived price, product quality and Brand Image Against Purchasing Decisions. Keywords: Perceived Price, Product Quality, Brand Image, Purchase Decision